Productivity enhancement in a wood furniture manufacturing factory by improving work procedures and plant layout - Korrakot Yaibuathet Tippayawong (2018)
The objective of this study is to improve productivity of a furniture manufacturing company. Motion and time study, process analysis and plant layout design were used as tools to improve the process. Simulation was carried out to evaluate the designed layout. Initially, production process was analyzed to evaluate process operation time. Preliminary survey showed that there were some redundant and duplicate processes, and many waiting periods. The existing production process was inefficient, showing bottleneck. New plant layouts were proposed to enable more balanced and smoother production process flow. From the proposed method, distance of the production flow can be shortened from 155 m to about 45 m. The production time can be reduced from about 260 min to 215 min, resulting in more than 15% increase in productivity.